Death in paradise. Season three [videorecording (DVD)] - Miller, Ben, 1966-; Martins, Sara, 1977-; John-Jules, Danny (Warner Home Video, 2014)
Bringing a dose of sunshine back to the small screen, the series returns for a third season of impossible murders on the beautiful Caribbean island of Saint Marie.